2008
DOI: 10.1158/1078-0432.ccr-08-0478
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Tumor and Plasma Levels of hTERT mRNA in Patients with Colorectal Cancer: Implications for Monitoring of Neoplastic Disease

Abstract: Purpose: Colorectal cancer (CRC) is one of the most common cancers in western countries.Identification of circulating markers for CRC would optimize early stage diagnosis and the monitoring for disease recurrence. Expression of telomerase reverse transcriptase (hTERT) is essential to the oncogenic process and might be used as a molecular marker of neoplastic disease. Experimental Design: Eighty-five CRC samples (25 stage I, 15 stage II, 15 stage III, and 30 stage IV), the available corresponding noncancerous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 41 publications
7
85
0
Order By: Relevance
“…We did not find any relationship between telomere length and tumour progression. In agreement with previous studies (Terrin et al, 2008), levels of hTERT increased with tumour progression; it is conceivable that telomere length may stabilise with tumour progression because of an increase in telomerase activity compensating for replicative telomere loss. It should be pointed out that B15% of CRCs presented MSI-H, whereas the p53 gene is the known major genetic alteration in CRCs with MSS (Kim et al, 2007;Ogino et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not find any relationship between telomere length and tumour progression. In agreement with previous studies (Terrin et al, 2008), levels of hTERT increased with tumour progression; it is conceivable that telomere length may stabilise with tumour progression because of an increase in telomerase activity compensating for replicative telomere loss. It should be pointed out that B15% of CRCs presented MSI-H, whereas the p53 gene is the known major genetic alteration in CRCs with MSS (Kim et al, 2007;Ogino et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…The quantification of all hTERT transcripts (hTERT-AT) in CRC samples was carried out by real-time PCR, exactly as previously described (Terrin et al, 2007(Terrin et al, , 2008, and normalised for 10 3 copies of the housekeeping hypoxanthine guanine phosphoribosyl transferase 1 (HPRT1) gene (Terrin et al, 2008).…”
Section: Quantification Of Htert Transcriptsmentioning
confidence: 99%
“…Similarly the presence of exRNA is well documented in sera/plasma from patients presenting with breast [62][63][64] and colon cancers [65,66].…”
Section: Circulating Nucleic Acids and Cancermentioning
confidence: 99%
“…Detection of hTERT expression either in plasma [65,112], peripheral blood mononuclear cells [113] or by IHC in primary tumors [114] has been identified as diagnostic for prostate, colon, esophageal cancers, and paragangliomas, respectively. In terms of breast cancer, Chen et al [97] identified hTERC and hTERT mRNA in primary tumors and sera of breast cancer patients presenting with invasive lobular carcinoma and invasive ductal carcinoma.…”
Section: Human Telomerase Reverse Transcriptasementioning
confidence: 99%
“…3B). Though previous studies have reported an association between hTERT expression levels and disease progression in colorectal cancer [47][48][49], these studies primarily looked at hTERT transcript levels. Here, 78% of colon tumours expressed hTERT protein, 8% of which had nuclear hTERT expression, similar levels of hTERT expression in colorectal tumours have been previously reported [50].…”
Section: Ruvbl2 Impacts Htert Activity and Associates With Htert Exprmentioning
confidence: 99%